An Integrated Information System Model for Optimizing Bulk Water Distribution - Abdullah, Siti Sarah; Sumirat, Tubagus Rusli (Teknik Informatika Universitas Suryakancana Cianjur, 2025)
Many companies in the bulk water distribution sector still rely on manual recording systems, which often lead to scheduling conflicts, delivery inaccuracies, and inefficient payroll management. Recent studies highlight the need for integrated information systems to optimize logistics and operational efficiency in similar industries. This study aims to design and implement an integrated information system model to optimize the distribution of bulk water from suppliers to drinking water depots. The research adopts a qualitative approach, combining literature review, field observation, and in-depth interviews. System design follows the Waterfall model, with UML modeling and Black Box Testing for validation. The developed system successfully automates scheduling, generates delivery orders, recapitulates shipment data, and manages driver payroll. Empirical testing showed scheduling time was reduced from 45–60 minutes to 10–15 minutes ( 75% faster), payroll reporting from 2–3 hours to under 30 minutes ( 80% faster), and data recap from up to 2 hours to instant ( 100% faster). All functions were validated through testing, showing no logical errors. The integrated information system model significantly improves the efficiency, accuracy, and effectiveness of bulk water distribution. Future research may incorporate mobile technology and GPS tracking for enhanced real-time monitoring.